Fatigue life prediction of double-row tapered roller bearings considering thermal effect - Taewoo Kim; Junho Suh; Jeongin Lee; Bora Lee; Yonghun Yu (Advances in Mechanical Engineering, 2023)
Thermal effects on fatigue life were investigated by analyzing the thermomechanical behavior of double-row tapered roller bearings (DTRBs) and a fatigue life prediction model was developed. A bearing’s mechanical behavior was analyzed using a quasi-static model and its thermal behavior was analyzed using a thermal network method. Viscous drag and sliding friction at the contact area were considered as heat generation factors for DTRBs. The bearing lubrication characteristics and shape dimensions interacted with the temperature and the analysis was repeated until the entire DTRB system’s temperature converged. DTRB fatigue life was estimated using a fatigue life formula based on Gupta and Zaretsky’s statistical model. Results confirmed that the fatigue life decreased rapidly because of an interference fit that occurred at very high rotation speeds or at very low supply oil flow rates. This interference fit phenomenon is caused by thermal expansion of the bearing element. The interference fit can be prevented by designing with a large initial clearance value, but an initial clearance that is too large affects fatigue life negatively because of load distribution imbalance. Optimal design of the roller end sphere radius to minimize sliding friction for the flange part can provide additional help in preventing interference fit.